Human Rights in Ayurvedic Literature - Kumar, Pathak Arvind; Rashmi, Diwan; Reetika, Pathak (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is an integral part of Indian culture. It is counted in such texts of the world from which humans have gained inspiration for personal behavior and social creation. In the Ayurveda Samhita, various rules are considered to be the best for healthy and happy living, even in a healthy and disease state. Aim of Ayurveda to maintain health and remove the disease of the patient. In both the conditions, Ayurveda gives the rights to use it independently to the entire universe. How properly you use this authority depends on the individual. The question in this is not only about religious, faith, or medicinal. Every social person has this expectation and aspiration to meet the needs of human life, in any way, by mutual cooperation and in an elegant way. Human rights are holding up the inspiring vision of a free and peaceful world and set minimum standards for how both individuals and institutions should treat people. They also empower people to take action to demand and defend their rights and rights of others. Some rights for themselves, some for public and some are related to women’s and children. It is necessary to follow them in every condition. Indian Penal code provision punishment for improper use of these rights.